Pemberdayaan Anak-Anak TK dengan Pembelajaran Kosa kata & Numerasi Berbasis Fun Game dan Education - Ni Made Rianita (Jurnal Inovasi Pengabdian Masyarakat, 2024)
Many aspects of human life have changed due to advances in science and technology. Education is the key to the country’s future development and it starts from early childhood to adulthood. Therefore, changes and improvements continue to be made in various education sectors. In this case, the researcher wants to apply a learning media called "DUDADADU.EDU", a learning based on fun games and education that teaches vocabulary and numeracy. The aim of this activity is to increase the interest and enthusiasm of children at the Kumara Satya Dharma Kindergarten. This activity is carried out using the STAD cooperative learning model, which emphasizes activity and interaction between students to help each other in mastering the material. The aim of this service is to increase the interest and motivation of children at the Kumara Satya Dharma Kindergarten. The expected outcomes of this activity include an impact on children’s learning at school as well as in their surrounding environment.